Modul Praktikum Implementasi Load Balance pada Web Server dengan Algoritma Round Robin Menggunakan Banana Pi - Candra Setiya Fajriawan (Jurnal Jaringan Telekomunikasi, 2017)
Websites that have high traffic rates will have a large load of access. If the web server uses a single server topology, the work of the web server is getting heavier in receiving the request, so that problems such as crashes or downs arise due to the many requests from clients.From the test results, it was found that the load balance response time was slower than thatsingle web server. The highest request loss on the load balance namely the number of clients 500 with 10000 requests amounting to 4.058% while the single web server on the number 500 clients with 10 000 requests for 10.622%. The value of throughput load balance and a single web server have the same average value, but load balance is able to equalize the throughput on all clients anda single web server is incapable of doing that. Banana Pi device used as a web The server is able to handle simulated DoS attacks on the HTTP protocol with a maximum value of use The CPU is 52% while using a load balance that makes 2 web servers work together able to reduce CPU usage by 19%.